Mr. Malcolm's list [videorecording (DVD)] - Allain, Suzanne; Pinto, Freida, 1984-; Dirisu, Sope, 1991-; Jackson-Cohen, Oliver, 1986-; Croll, Doña; Mori, Naoko, 1975-; Park, Ashley; Ashton, Zawe; James, Theo, 1984-; Miller, Tony, 1964-; Warner, Amelia, 1982-; Allain, Suzanne (Decal, 2022)
In nineteenth-century England, jilted by London's most eligible bachelor, Julia convinces her friend to play the role of his ideal match. Soon, Mr. Malcolm wonders whether he's found the perfect woman or the perfect hoax.